ARGUMEN KEBOLEHAN WANITA BEKERJA DI LUAR RUMAH PERSPEKTIF AL-QUR’AN (STUDI PEMIKIRAN NADIA ABDURRAHMAN DAN OKI SETIANA DEWI) - Shonhaji, Siti Qurrotul Aini; Badriyah, Noviyatul (IAINU Kebumen Prodi IAT, 2023)
Women are one of God's creatures who are very privileged so that a woman's position cannot be replaced by another God's creature. Discussions about women continue to be echoed in society, especially regarding career women. Discussions about career women are also of interest to Muslim scholars who discuss career women in the Koran, including Nadia Abdurrahman and Oki Setiana Dewi. The understanding of career women in the Qur'an was raised by contemporary women with different backgrounds, namely Nadia from the Islamic boarding school and Oki from the preacher circle, which made the author interested in conducting a comparative study of the understanding of these two figures. The focus of this research is as follows: 1) What is the urgency of Nadia Abdurrahman's thoughts regarding the ability of women to work outside the home from the perspective of the Qur'an? 2) What is the urgency of Oki Setiana Dewi's thoughts regarding the ability of women to work outside the home from the perspective of the Qur'an? 3) What are the similarities and differences in the thoughts of Nadia Abdurrahman and Oki Setiana Dewi regarding the ability of women to work outside the home from the perspective of the Koran? This research uses a type of qualitative research using the netnography method, while the approach of this research is a comparative study between the thoughts of Nadia Abdurrahman and Oki Setiana Dewi. The data collection techniques for this research include: determining the theme, searching and collecting data, transcribing several videos that have been collected, observing the data that has been obtained from the YouTube channel, carrying out analysis of the data that has been obtained. The results of this research were that: 1) Nadia explained that a woman is allowed to have a career like a man and if the work is done with good intentions it will be rewarded by Allah SWT., 2) Oki explained that a woman can go out home and have a career like women at the time of the Prophet saw with certain conditions as explained. 3) Nadia Abdurrahman and Oki Setiana Dewi's opinions regarding career women in the Koran have the same explanation regarding a woman's ability to have a career outside the home. Meanwhile, the difference between the two lies in the legal origin of career women, the characteristics or methods of understanding verses of the Koran and the educational background of both.